Relationships between Body Image Perception and Body Esteem and Sexual Assertiveness of Female College Students: Comparision of Nursing Students and Non-nursing Students (Medico Legal Update, 2021)
This study aimed to identify the relationships between body image perception and body esteem and sexualassertiveness of 296 female college students of university in Chungnam province: 150 nursing and 146non-nursing students. Data were collected using a self-administered questionnaire from November 1 toSeptember 10, 2018. The IBM SPSS 20.0 program was used to analyze collected data, including descriptivestatistics, t-test, one way ANOVA (Scheffe test for post-hoc) and Pearson’s correlation. Sexual assertivenessdid not differ between nursing and non-nursing students. In nursing students, the higher the appearnaceesteem, the higher the sexual assertiveness; however, differences in sexual assertiveness according tobody image perception were not significant. In non-nursing students, the higher the appearnace esteem,attribution esteem, and body weight esteem, the higher the sexual assertiveness, which was also higherin students who underestimate their body than those who did not. These results indicated that appearanceesteem of female students were related to sexual assertiveness. Therefore, various interventions to increasethe appearance esteem and promote positive perception about their body should be provieded to increase thesexual assertiveness of female college students.